To Lend or Not to Lend: The Bank of Japan’s ETF Purchase Program and Securities Lending - Katagiri, Mitsuru; Shino, Junnosuke; Takahashi, Koji (The Review of Asset Pricing Studies, 2025)
Abstract This study investigates the role of passive investors in the equity lending market by utilizing the expansion of exchange-traded fund (ETF) markets due to the Bank of Japan’s (BOJ) ETF purchasing program. We find that the BOJ’s purchases increase equity prices particularly for stocks with limited availability in the equity lending market. However, over the longer term, the BOJ’s cumulative purchases reduce lending fees, thus weakening the program’s effects. These findings suggest that ETF managers supply stocks that constitute ETFs to the equity lending market, and the lending behavior of ETFs, influenced by the BOJ’s program, alleviates short-selling constraints. (JEL E52, E58, G12, G14)